Feathers for peacock - Jules, Jacqueline, 1956-; Cann, Helen, 1969- (Bloomington, Indiana : Wisdom Tales, 2016)
Relates how through the generosity of birds of all shapes and sizes Peacock was given the biggest, most colorful feather coat of all.
Ages 4 and up.
Keywords: Peacocks -- Fiction; Birds -- Fiction; Feathers -- Fiction; Generosity -- Fiction